2020
DOI: 10.1186/s12970-020-00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of skim milk and isotonic drink consumption before exercise on fluid homeostasis and time-trial performance in cyclists: a randomized cross-over study

Abstract: Background: Hydration status affects endurance performance. Pre-exercise hydration recommendations target the consumption of high carbohydrate and sodium beverages. Milk, due to its carbohydrate and sodium content, may be considered an effective pre-exercise hydration beverage. Purpose: In a randomized cross-over trial, we compared the effects of an isotonic sport drink (SPD) with skim milk (SM) consumption before a race, on fluid homeostasis and time-trial performance in road cyclists. Methods: Male road cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Interestingly, similar results were obtained in a study of elite soccer players from the Spanish La Liga (Barcelona FC), in this group fewer than 30% of the subjects were euhydrated prior to training sessions (Rollo et al, 2021). This finding is consistent with previous observations that many athletes are poorly hydrated before training sessions (García-Berger et al, 2020). In a study of recreational basketball players, an at all astonishing 17.5% of subjects reported that they did not drink before exercise (Bibiloni et al, 2018).…”
Section: Hydrationsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, similar results were obtained in a study of elite soccer players from the Spanish La Liga (Barcelona FC), in this group fewer than 30% of the subjects were euhydrated prior to training sessions (Rollo et al, 2021). This finding is consistent with previous observations that many athletes are poorly hydrated before training sessions (García-Berger et al, 2020). In a study of recreational basketball players, an at all astonishing 17.5% of subjects reported that they did not drink before exercise (Bibiloni et al, 2018).…”
Section: Hydrationsupporting
confidence: 91%
“…Hypohydration greater than 2% of body mass impairs performance during endurance exercise, decreases physical work capacity and has a negative impact on mood ( Sawka and Montain, 2000 ; Sawka et al, 2007 ; Seo et al, 2014 ; Bibiloni et al, 2018 ; García-Berger et al, 2020 ). The risk of rhabdomyolysis, exercise-associated hyponatremia and acute kidney injury (AKI) is increased in subjects with a body water deficit ( Krisher et al, 2020 ; Juett et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes usually drink water or sports drinks (SpD) to rehydrate during training and competition. This effect has been demonstrated in several studies [10,15,16]. Still, one can also hydrate with water alone or with an oral rehydration solution (ORS) containing water with traces of sugar, salt, sodium, and potassium.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, these formulations may increase fluid retention and have mild hypervolemic effects; therefore, they may ameliorate dehydration during exercise, without the risk of possible adverse effects often observed with other hyperhydration protocols. Unfortunately, most research on the pre-exercise period has focused on maximizing glycogen stores to ensure adequate fuel supply during exercise, with only a few food products, such as coconut water, skimmed milk, non-alcoholic beer, and soup being explored to improve pre-exercise hydration status [ 195 , 196 , 197 , 198 ]. A rationale for the type, volume, and timing of pre-exercise hydration is not always clear, and further research on well-designed CES compositions to improve fluid balance before exercise is warranted.…”
Section: Impact Of Exercise Timing On Carbohydrate–electrolyte Solutionsmentioning
confidence: 99%